Implimentasi Pedoman Keberlajutan Destinasi Pura Puseh Desa Batuan Kabupaten Gianyar, Bali - I Gusti Ngurah Agung Wiryanata; I Wayan Sunarsa; Christina Susanti (Journal of Tourism and Hospitality Analysis (JoTHA), 2025)
This research wants to know the implementation of the sustainability guidelines for the Puseh Batuan Temple destination, Gianyar Regency. The analysis technique used is descriptive qualitative with stages of qualitative data analysis, namely data reduction, data presentation and drawing conclusions. The research results show that the destination has carried out sustainability according to the sustainability guidelines of the Minister of Tourism Regulation. The Puseh Temple destination carries out sustainable management, by having a clear organizational structure, management involving the government and the community. Stakeholder engagement to manage stress and change. Social and economic sustainability by providing local economic benefits, and social welfare and impact. The Puseh Batuan Temple destination opens up employment opportunities for local residents. This has an impact on people's social life. Cultural sustainability by making rules for tourists to maintain culture, preserving cultural heritage and making rules for visitors to wear traditional Balinese clothing. Environmental sustainability by conserving natural heritage, managing resources and managing waste and emissions. Natural heritage conservation and resource management are carried out by creating a parking lot with a beautiful garden. Waste and emissions management by placing trash bins according to the type of waste.